Whole Grain Intakes in the Diets Of Malaysian Children and Adolescents – Findings from the MyBreakfast Study - AK, Norimah (PLoS One, 2015)
BACKGROUND: Diets rich in whole grain are associated with several health benefits. Little is known however, about whole grain consumption patterns in Malaysia. The aim of this study was to assess whole grain intakes and dietary source in Malaysian children and adolescents. METHODS: This analysis is from the MyBreakfast study, a national cross sectional study investigating eating habits among primary and secondary school children throughout Malaysia, conducted in 2013. Children (n = 5,165) and adolescents (n = 2,947) who completed two days of dietary assessment using a food record or recall respectively were included. The whole grain content of foods was estimated mainly through the use of quantitative ingredient declarations on food labels. All wholegrain foods were considered irrespective of the amount of whole grain they contained. RESULTS: Overall, only 25% of children and 19% of adolescents were wholegrain consumers. Mean daily intakes in the total sample were 2.3g/d (SD 5.8g/d) in children and 1.7g/d (SD 4.7g/d) in adolescents and in the consumer’s only sample, mean intakes reached 9.1g/d (SD 8.6) and 9.2g/d (SD 7.1g/d) respectively. Wheat was the main grain source of whole grain while ready to eat breakfast cereals and hot cereals were the main food contributors. Less than 3% of the children and adolescents reached the US quantitative whole grain recommendation of 48g/day. CONCLUSION: Whole grain is consumed by only a minority of Malaysian children and adolescents and even among consumers, intakes are well below recommendations. Efforts are needed to firstly understand the barriers to whole grain consumption among Malaysian children in order to design effective health promotion initiatives to promote an increase in whole grain consumption.